Effects of photosynthetic nitrogen use efficiency on dry matter distribution in rice under drought–flood abrupt alternation stress - Gao, Yun; Zhu, Rui; Ma, Chunya (Paddy and water environment, 2025)
Parameters related to photosynthetic nitrogen use efficiency (PNUE) are key contributors to rational dry matter distribution and improvements in the spike weight of rice. However, it is unclear whether the interaction effects of drought–flood abrupt alternation (DFAA) have an antagonistic compensation effect or a superimposed reduction effect on PNUE. The experiment included six DFAA groups, six single drought groups, six single flood groups and one normal irrigation group. The mechanisms by which the interactions of DFAA affected the PNUE and dry matter distribution of rice during different periods were investigated. The results revealed that early drought stress of DFAA promoted the recovery of the photosynthetic rate, and later flooding stress increased of DFAA the leaf nitrogen content and specific leaf weight. Long-term moderate drought had a certain compensation effect on the PNUE of rice plants under nonsevere flooding conditions. Recovering the PNUE and photosynthetic rate promoted the distribution of total dry matter to the roots, and the leaf nitrogen content was the main factor limiting stem growth. This study suggests that moderate drought exercise in the early stage is more conducive to improving rice PNUE. The depth and duration of water retention should be controlled during the flooding period, and appropriate manual intervention should be carried out to increase the leaf nitrogen content and flood tolerance and panicle weight. These results provide a theoretical basis for analyzing the stress resistance response mechanism of plants under DFAA.